Body mass index and mortality in chronic obstructive pulmonary disease: A dose–response meta-analysis. Issue 28 (July 2016) - Guo, Yibin; Zhang, Tianyi; Wang, Zhiyong; Yu, Feifei; Xu, Qin; Guo, Wei; Wu, Cheng; He, Jia
Abstract : Abstract: The aim of this study is to summarize the evidence on the dose–response relationship between body mass index (BMI) and mortality in patients with chronic obstructive pulmonary disease (COPD). We performed a systemic literature search in PubMed, Embase, and Web of Science for relevant studies that were published until June 2015. A random effects meta-analysis was used to estimate the pooled relative risks (RRs) of all-cause mortality in COPD patients with normal weight compared with those who were underweight, overweight, or obese. In addition, a dose–response meta-analysis was conducted to explore the dose–response relationship between BMI and all-cause mortality in COPD patients. A total of 17 observational studies involving 30, 182 COPD patients among 285, 960 participants were included. Compared with the reference category, the RRs of underweight, overweight, and obese individuals were 1.40 (95% confidence interval (CI), 1.20–1.63), 0.80 (95% CI, 0.67–0.96), and 0.77 (95% CI, 0.62–0.95), respectively. A significant nonlinear relationship between BMI and mortality of COPD patients was found by using a random effects model. COPD patients with BMI of <21.75 kg/m 2 had a higher risk of death. Moreover, an increase in the BMI resulted in a decrease in the risk of death. The risk of death was lowest when BMI was 30 kg/m 2 (RR = 0.69; 95% CI, 0.53–0.89). The BMI was not associated with all-cause mortality when BMI was >32 kg/m 2 . Our findings indicate that overweight is associated with a lower risk of all-cause mortality among patients with COPD whereas underweight is associated with a higher risk of all-cause mortality in these patients. However, there is limited evidence to support the association between obesity and the risk of all-cause mortality in patients with COPD.